KLASIFIKASI DAUN BIDURI (Calotropis gigantea L.) DARI LOKASI BERBEDA MENGGUNAKAN SPEKTROSKOPI INFRAMERAH DAN KEMOMETRIK - Zahara, Hafni; Karma, Taufiq; Yusuf, Muhammad (Lantanida Journal, 2023)
In this study, FTIR spectroscopy paired with PCA was utilized to differentiate biduri plants from different places. All biduri leaf samples from each location were then obtained for their FTIR spectrum in the wave number range of 4000-400 cm-1 and pretreated with the 1st derivative. The preprocessed spectrum was then examined using HCA and PCA chemometric methods; based on the HCA classification results, the biduri samples were divided into three groups, but the selected groups were unable to identify the biduri samples from the geothermal manifestation area. The PCA findings displayed in the plot scores then successfully classified the biduri leaf samples into four groups, with a total variance explained by 63% (PC1 44% and PC2 19%). This developed method can be used to correctly identify biduri plants originating from the geothermal manifestation area of Mount Seulawah Agam, allowing it to be concluded that environmental conditions in the geothermal manifestation area of Mount Seulawah Agam affect the content of secondary metabolites present in biduri plants, as evidenced by the PCA plot, which shows samples from geothermal and non-geothermal locations forming their respective groups.